Tratamiento contable de las mermas en la empresa FERRO STEEL S.A. y su impacto en los estados financieros - Febre Centeno, Claudia Paola (2019)
This research study entitled Accounting treatment of waste in the company FERRO STEEL S.A. and its impact on the financial statements analyzes the production of the waste and its effect on the entity's financial statements. To do this, the context in which the study problem is developed was analyzed. In order to carry out a survey and information processing, it was necessary to esign a methodology with a qualitative approach and conduct interviews and surveys of employees involved in the treatment of raw materials, waste generation and accounting records……..